Traditional and Modernized Characteristics of Registered and Unregistered Family Day Care Providers - Cox, Danetta; Richarz, Sherrill ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
Registered and unregistered family day care providers were questioned regarding their "traditional" (less professionalized) and "modernized" (more professionalized) characteristics as described in Wattenberg's (1977) study of certified family day care providers. Data showed that unregistered providers had significantly less experience than registered providers as members of the labor force outside the home, and that registered providers had significantly more training and information on child care topics. Unregistered providers did, however, request more information on child care topics. In addition, unregistered providers had significantly more children in care than did providers in the registered group. The two groups were not significantly different on other variables in the survey. (PCB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Certification; Child Caregivers; Family Day Care; Occupational Surveys; Professional Associations; Professional Development; Professional Training; Qualifications; Reports, Research